COVID-19: Prevention Strategies - Buran, Duran; İlhan, Mustafa N (Turkey Health Literacy Journal, 2021)
The current outbreak of the novel coronavirus SARS‐CoV‐2 (coronavirus disease 2019; previously 2019‐nCoV), epi‐centred in Hubei Province of the People’s Republic of China, has spread to many other countries. This outbreak is a serious public health problem affecting the whole world. Prevention strategies are key to success in controlling an pandemic. Therefore, this paper examined COVID-19 prevention strategies (primary, secondary and tertiary prevention strategies )and key points related to mask wearing, hand hygiene, social distance and COVID-19 vaccines.
Keywords: COVID-19, outbreak, prevention strategies ,preventive measures, wearing masks, hand hygiene, social distance, COVID-19 vaccines